Pengaruh Brand Awareness, Kualitas Produk, dan Harga terhadap Keputusan Pembelian Samsung - L. Jordan Leroya; Vonny Tiara N (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: One of the best-selling cellphone brands in Indonesia is owned by the Samsung brand. The purpose of this study is to analyze how brand awareness, product quality, and price affect the purchase decision of Samsung mobile phones. Methodology: The method applied is quantitative by including validity, reliability, multiple linear regression, hypothesis testing (t test and f test), and determination coefficient testing. The results of the study partially state that brand awareness, product quality, and price have a positive effect on purchasing decisions. Results: The results of the study partially state that brand awareness, product quality, and price have a positive effect on purchasing decisions. The results simultaneously show that the three variables have a positive influence on purchasing decisions by 66% on the decision to purchase samsung cellphones at Bandar Lampung University. Conclusions: Samsung smartphone purchase decisions among Universitas Bandar Lampung students are positively influenced by brand awareness, product quality, and price. Limitations: The limitations of this study in terms of collecting respondents are only 102 respondents and in terms of variables covering 3 variables. Contribution: This research is useful for the Samsung company itself as a reference in marketing Samsung cellphone products.